HOME AS A TRADITION IN THE STORIES OF MADZUNKOV - Markovska, Slavica Urumova (PALIMPSEST / ПАЛИМПСЕСТ, 2019)
A home that is in the spirit of tradition in the stories of Madzunkov is an interesting field of research in which different domains are interlaced - he compares the home as protection vs. home as a thread, home vs. family, looking for the place of the mother in the home and the proper place to create a home; reveals what happens when we are far away from home, and how the memories fort the home are created. This research emphasizes the interpretation of the short stories of Madzunkov and their impact on the growth of the narrator. For this analysis, the crucial value is the tradition in which the past has left a precious mark, and the present has enhanced and enriched the stories of Madzunkov. From the analysis it can be concluded that the old and rich Macedonian tradition has mixed with advancement and modern life in the most beautiful way, and so united, they together represent a completeness that holds all the elements of a culture that is based on its customs in centuries. The first association of home is always family, on which Madzunkov recalls in many stories. The home occupies the thoughts of the narrator with the highest attention, and also enhances and saddens at the same time.